Optimización de films de azopolímero para aplicaciones de memoria óptica, usando etilenglicol como generador de volumen libre - Tambosco, Franco Lucio (2023)
Azopolymers are well known for their photo-induced properties, in particular, the photoinduced birefringence. Improving their performance has been of great interest in recent years for the development of applications as, for example, polarization holography, lithography and optical storage. In this work, we present the optimization of the azopolymer for optical memory applications by using ethylene glycol as a free-volume generator. Thin films were fabricated with Poly[1-[4-(3-carboxy-4-hydroxyphenyl-azo) benzenesulfonamido]-1,2-ethanediyl, sodium salt] (PAZO) and ethylene glycol at different % w/w concentrations. Samples were characterized by measuring the birefringence during recording, relaxation and erase cycles. The measured glass transition temperature (Tg) showed a minimum for the concentration 40 %w/w, at which the degree of decay, D=1−ΔnREM/ΔnMAX, reaches a maximum. Birefringence was also simulated using a stochastic model that includes the key factors involved in the recording process. We show that the material can be optimized for optical memories storage applications by balancing the free volume with the azobenzene concentration. This causes a decrease in the amount of azobenzenes while maintaining the efficiency of the samples.